2021
DOI: 10.1177/20543581211022207
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health Deterioration Among Older New Zealanders Undergoing Dialysis: A Three-Year Accelerated Longitudinal Cohort Study

Abstract: Background: Patient involvement in dialysis decision-making is crucial, yet little is known about patient-reported outcomes over time on dialysis. Objective: To examine health-related outcomes over 24 and 36 months in an older cohort of dialysis patients. Design: The “Dialysis outcomes in those aged ≥65 years study” is a prospective longitudinal cohort study of New Zealanders with kidney failure. Setting: Three New Zealand nephrology units. Patients: Kidney failure (dialysis and predialysis) patients aged 65 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Patients with ESRD have multiple co-morbid conditions including diabetes and hypertension, and are more prone to renal-related complications such as imbalance in calcium and phosphate homeostasis, vitamin D deficiency, anemia, and secondary hyperparathyroidism [ 2 4 ], which together may significantly impact patients’ well-being and health outcomes. Additionally, maintenance dialysis by itself is an invasive procedure which subjects patients to additional pain and discomfort [ 5 ]. Anemia is prevalent in CKD, especially in patients receiving dialysis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ESRD have multiple co-morbid conditions including diabetes and hypertension, and are more prone to renal-related complications such as imbalance in calcium and phosphate homeostasis, vitamin D deficiency, anemia, and secondary hyperparathyroidism [ 2 4 ], which together may significantly impact patients’ well-being and health outcomes. Additionally, maintenance dialysis by itself is an invasive procedure which subjects patients to additional pain and discomfort [ 5 ]. Anemia is prevalent in CKD, especially in patients receiving dialysis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Few studies have investigated health-related quality of life (HRQoL) among older individuals experiencing kidney failure. Previous findings from our longitudinal dialysis outcomes in older New Zealanders study (DOS65+ study) 19,20 have found that HRQoL, as measured by the EQ-5D-3L, 21 is an important determinant of subsequent overall health reported among older people treated for kidney failure. However, it appears that no studies have yet been published reporting HRQoL in relation to disability outcomes for this older age group with kidney failure-including for those on dialysis.…”
Section: Introductionmentioning
confidence: 80%
“…The main objective of this analysis was to determine if HRQoL at baseline, measured using the EQ-5D-3L, 20 predicted disability outcomes as measured by the WHO Disability Assessment Schedule (WHODAS) 2.0 29 12 months later. The EQ-5D-3L 20 asks about health status today across 5 dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) with 3 responses per dimension assessing the problem severity (ie, no, moderate, or extreme).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation